Quality of life, adherence to voice rehabilitation therapy and psychological variables in patients with head and neck cancer - Toski de Angel, Evelin; Galindo-Vázquez, Oscar; Contreras Buendia, Marlen; Espinoza Bello, Marcos; González Ling, Ana Marcela; Ramos Fuentes, Shugely Karolina (Psicooncología, 2024)
Introduction: Voice problems can affect quality of life (QoL), other psychological aspects, and the adequate adherence to voice rehabilitation therapy. Objective: To determine the association between QoL and treatment adherence (TA) to voice rehabilitation with symptoms of anxiety, depression, and coping strategies. Method: A longitudinal study was conducted with 97 participants with head and neck cancer (H&N) who were attending voice rehabilitation therapy. Instruments: EORTC QLQ-C30 and QLQ-H&N35, Treatment Adherence Checklist, Cancer Coping Questionnaire and HADS. Results: The mean overall QoL was 83.33, and mean TA was 8.80. Lower overall QoL and emotional functioning scores, as well as higher dry mouth scores were associated with higher levels of anxiety. Greater problems with social contact and lower TA were associated to higher depression scores. Conclusion: Consistent with the literature, TA and QoL were associated to depression and QoL was also correlated to anxiety. These results are among the first to explore such aspects in Latino patients and emphasize the importance of multidisciplinary care for H&N cancer patients in voice rehabilitation therapy, given that during their treatment they may encounter psychological barriers that could hinder their progress in voice quality and QoL.
Keywords: Adherence; anxiety; depression; head and neck cancer; quality of life; voice rehabilitation